2007
DOI: 10.1128/mcb.02254-06
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Release of Eukaryotic Translation Initiation Factors 5B and 1A from 80S Ribosomes following Subunit Joining

Abstract: The translation initiation GTPase eukaryotic translation initiation factor 5B (eIF5B) binds to the factor eIF1A and catalyzes ribosomal subunit joining in vitro. We show that rapid depletion of eIF5B in Saccharomyces cerevisiae results in the accumulation of eIF1A and mRNA on 40S subunits in vivo, consistent with a defect in subunit joining. Substituting Ala for the last five residues in eIF1A (eIF1A-5A) impairs eIF5B binding to eIF1A in cell extracts and to 40S complexes in vivo. Consistently, overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 38 publications
(77 reference statements)
7
99
1
Order By: Relevance
“…Blocking eIF5B GTPase activity, either by inclusion of nonhydrolyzable GTP analogs or by mutation of the eIF5B G domain, does not impair subunit joining (Shin et al , 2007Acker et al 2009); however, it does impede eIF1A release from 80S ribosomes both in vivo and in vitro (Fringer et al 2007;Acker et al 2009). Mutations that disrupt the GTPase activity of eIF5B severely impair yeast cell growth (Shin et al , 2007.…”
Section: Subunit Joiningmentioning
confidence: 99%
See 2 more Smart Citations
“…Blocking eIF5B GTPase activity, either by inclusion of nonhydrolyzable GTP analogs or by mutation of the eIF5B G domain, does not impair subunit joining (Shin et al , 2007Acker et al 2009); however, it does impede eIF1A release from 80S ribosomes both in vivo and in vitro (Fringer et al 2007;Acker et al 2009). Mutations that disrupt the GTPase activity of eIF5B severely impair yeast cell growth (Shin et al , 2007.…”
Section: Subunit Joiningmentioning
confidence: 99%
“…Domain IV of eIF5B binds to eIF1A via interaction with the last five residues at the C terminus of eIF1A (Olsen et al 2003;Acker et al 2006;Fringer et al 2007). Mutation of the eIF1A C terminus impairs subunit joining and full activation of eIF5B GTPase activity in vitro (Acker et al 2006) and impairs yeast cell growth and eIF5B binding to 40S complexes in vivo.…”
Section: Subunit Joiningmentioning
confidence: 99%
See 1 more Smart Citation
“…28,63,64 It also plays a role, along with eIF5B, in ensuring proper subunit joining and formation of elongation-competent 80S ribosomes. 28,63,64 Hydroxyl radical probing and structural modeling involving eIF1A and Tetrahymena thermophila 40S ribosomal subunits (based on bacterial 30S:IF1 complex information) at »3.9A suggested that eIF1A resides near the A-site and makes contacts with eukaryotespecific proteins eS27 and eS30 as well as conserved protein uS12 which harbors eukaryote-specific extensions. 15,65 However, direct involvement of uS12 eukaryote-specific extensions in eIF1A binding has not been proven yet.…”
Section: E999576-6mentioning
confidence: 99%
“…Met base-pairs with the AUG, eIF5 stimulates eIF2-GTP hydrolysis, eIF2-GDP is released along with other factors, eIF5B-GTP is recruited to stimulate 60S ribosomal subunit joining, and eIF1A and eIF5B-GDP are released to generate the translationally active 80S complex (Fringer et al 2007;Hinnebusch et al 2007). After each round of initiation, eIF2-GDP must be recycled by eIF2B (a guanine nucleotide exchange factor) for a new round of initiation.…”
Section: Introductionmentioning
confidence: 99%